2021
DOI: 10.1002/jts5.119
|View full text |Cite
|
Sign up to set email alerts
|

Ya gotta wanna: Shifting motivational priorities in the self‐control process

Abstract: Self-control is widely regarded as beneficial for a variety of performance and well-being outcomes (e.g., academic success, eating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…In addition, Watson and Milfont (2017) found that self‐control predicted temporal considerations, which can be described as dispositional attitudes toward immediate and future consequences. Similarly, Vaghef et al (2021) found a positive relationship between delay of gratification and future time perspective. Given these connections with approach/avoidance of situations, temporal considerations, and future time perspective, it appears plausible that those higher in self‐control may tend to engage in more planning.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, Watson and Milfont (2017) found that self‐control predicted temporal considerations, which can be described as dispositional attitudes toward immediate and future consequences. Similarly, Vaghef et al (2021) found a positive relationship between delay of gratification and future time perspective. Given these connections with approach/avoidance of situations, temporal considerations, and future time perspective, it appears plausible that those higher in self‐control may tend to engage in more planning.…”
Section: Introductionmentioning
confidence: 84%
“…For self‐control‐to‐planning, previous research suggesting this relationship has focused on other aspects of the planning construct. For instance, Smit and Barber (2016) examined planning by using a problem‐solving rumination scale and Vaghef et al (2021) examined planning indirectly by investigating an individual's future time perspective. Thus, it may be that time management planning specifically (the focus of the current research) does not have the same connection with self‐control.…”
Section: Discussionmentioning
confidence: 99%